IDLE Challenges: Playing Digital Games? - Muhammad Najmussaqib Diya Alhaq; Nur Arifah Drajati; Agus Wijayanto (STAI Hubbulwathan Duri, 2021)
The purpose of this research is to examine the challenges faced by the learner and the activities they undertake concerning informal digital learning of English (IDLE) implementation in the English as foreign language (EFL) context. The impact of the COVID-19 on the education sector feels very challenging. Especially in EFL learning at the high/secondary school level, it is crucial since the skills are needed to support such level students' more complex need. It leads many experts to find the formal model's best alternative: playing digital games as IDLE. However, the current indications showed various challenges in the efforts of implementing IDLE within an academic context. As part of a more extensive sequential qualitative mixed-method study, seven high school students from various Indonesia parts were interviewed. From the findings, it is discovered that there were still some challenges regarding the implementation of IDLE in an academic context: physical and behavioural assumptions, dealing with the growth of physical and behavioural effect misconception and logical fallacy within the community; communal judgment, the a priori assumption of 'gaming stereotype' which massively wide-spread; and, technical challenges, regarding the implemental availability of the contemporary learning model. It is also recommended that finding solutions to these challenges requires many parties' involvement. It is due to some of the challenges were fundamentals. It is expected that many parties' involvement will make the resulting efforts to be a holistic solution.